Role of magnetic resonance urethrography in evaluation of male urethral stricture - Swain, S.; Behera, Kishore Kumar; Panda, S.; Tripathi, Abhilekh; Sharma, Sachin; Anshuman, Jateen; Manaharlal, Tilala Yash (International Surgery Journal, 2023)
Background: Urethral stricture in male is a common urological disease causing lower urinary tract symptoms like thin stream of urine with straining to urinate, may be associated with dysuria or acute urinary retention. RGU is gold standard in male urethral stricture evaluation. In this study we compare magnetic resonance urethrography (MRU) with retrograde urethrography (RGU) in diagnosing male urethral stricture. Methods: The 40 male patients with the diagnosis of stricture urethra were taken for this study. Evaluation done first by RGU then after 7 days MRU. Final corroboration of above findings with the surgery (endoscopic or open). Results: Data of 40 male patients with urethral stricture are analysed with computer software SPSS v 25. mean age of stricture diagnosis is 43 years (range is 31-63 years). Mean length of stricture is 1.90 cm (with SD 0.85), 1.89 cm (with SD 0.92) and 1.91 cm (with SD 0.94) in RGU, MRU and Surgery respectively. sensitivity and specificity of RGU is 84.2% and 50% and MRU is 92.1% and 100% respectively. accuracy of RGU and MRU is 82% and 92% respectively. 3 patients out of 16 patients with long segment bulbar urethral stricture (>1.5 cm) without any spongiofibrosis managed with BMG urethroplasty. Two patients out of 24 patients with short segment bulbar urethral stricture (<1.5 cm) with dense spongiofibrosis managed with PEEAU. Conclusions: Both RGU and MRU can detect stricture lengths accurately but MRU has advantage of detection of spongifibrosis in cases of anterior urethral stricture. MRU detects orientation and alignment of both proximal and distal urethral segments in case of PFUI.